Adherence to the Mediterranean diet to prevent or delay hepatic steatosis: a longitudinal analysis within the PREDIMED study - Cueto-Galán, Raquel; Fontalba-Navas, Andres; Gutiérrez-Bedmar, Mario; Ruiz-Canela, Miguel; Martínez-González, Miguel A.; Alves, Lilian; Babio, Nancy; Fitó, Montserrat; Ros, Emilio; Fiol, Miquel; Estruch, Ramón; Arós, Fernando; et al. (Frontiers in Nutrition, 2025)
BackgroundLittle is known about the potential preventive effect of adherence to the Mediterranean diet (MedDiet) on the development of metabolic dysfunction-associated steatotic liver disease (MASLD).AimThis study aims to determine the impact of adherence to the MedDiet on the progression of MASLD, measured using the hepatic steatosis index (HSI) at baseline and annually over a 5-year follow-up period within the framework of the PREvención con DIeta MEDiterránea (PREDIMED) study.MethodParticipants from the PREDIMED trial with sufficient available data (n = 3,145) were examined annually over 5 years. Adherence to the MedDiet was evaluated using the Mediterranean Diet Adherence Screener (MEDAS) questionnaire, and the presence/severity of hepatic steatosis was determined according to the HSI. Linear mixed models were used to analyze the association between the study variables and HSI.ResultsThe participants (57% female, 43% male) had a mean age of 67.2 (SD 6.2) years. Among the cardiovascular risk factors considered, the mean BMI was 29.81 (SD 3.62); 47% of participants had type 2 diabetes, 70% had hypercholesterolaemia, and 84% had hypertension. Over the 5-year follow-up, average adherence to the MedDiet and physical activity generally increased, while alcohol consumption, calorie intake, tobacco use, hypercholesterolaemia, and hypertension decreased. The fully adjusted multivariate model reflected a statistically significant decrease in the HSI per unit increase in adherence to the MedDiet (β = −0.075; 95% CI: −0.128, −0.021).ConclusionIn individuals at high cardiovascular risk, adherence to the MedDiet is significantly associated with improvements in HSI. These longitudinal findings highlight the important role of the MedDiet in delaying or slowing the natural progression of MASLD, contributing to both its prevention and clinical management.